Assessment of Academic Utilization of Online Information Resources by Undergraduate Students in University of Nigeria, Nsukka - Mole, Austin J.C. (International Journal of Knowledge Content Development & Technology, 2017)
ABSTRACT The research was undertaken to determine the academic utilization of online information resources by undergraduate students in the University of Nigeria, Nsukka. The objectives of the study were to identify the online information resources used by the students; academic purposes for their use, extent of their academic use, problems as well as strategies for improving the utilization of the online information resources by undergraduate students. Descriptive survey was used as the design of this study. The study was carried out in Nsukka, Enugu State in the South Eastern Geopolitical zone of Nigeria. The population of the study is made up of 25,657 students of the University of Nigeria, Nsukka. Six research questions were set to guide the study. The instrument for data collection is UOIRSQ (Utilization of Online Information Resources by Students’ Questionnaire) which was formulated in accordance with the research question. Since the research design is descriptive, likewise, descriptive method of data analysis was used in answering the research questions. The major findings were that out of many online information resources available, only few of them are used by undergraduate students. Wikipedia Online Encyclopaedia, Google Books and Punch/Vanguard are highly used. Problems and strategies for improving on the problems were given. Some of the recommendations made for enhancing the academic utilization of online information resources by students in the university include: providing more online training facilities to undergraduates in order to equip them on how to use online information resources; constantly upgrading the server’s bandwidth to ensure maximum service or faster navigation; providing and given to the students improved access to computer systems, preferably laptops, and also teaching them advanced searching skills through organisation of workshops and seminars by the library and university. URL: http://ijkcdt.net/xml/11661/11661.pdf